Violência doméstica patrimonial: dilemas e vulnerabilidades, a realidade de Manacapuru de 2018 a 2022. - Moraes, João Batista Flores de (2024)
The research is linked to line 1: Society, State, Culture and Public Security, of the Postgraduate Program in Public Security, Citizenship and Human Rights, at the State University of Amazonas. This is interdisciplinary research, involving various fields of human knowledge, such as sociology, psychology, and law, which were put into critical dialogue, from a historical-cultural process perspective. The objective of this research is to analyze property violence in the records of Police Inquiries from the Specialized Police Station for Women's Assistance, in the District of Manacapuru-AM, in the years 2018 to 2022, with the aim of characterizing property violence, profiling the perpetrator, victim, analyze the victim’s narrative and verify the existence of a protection network at the research site. The specific purpose of the study is the elaboration of the technical-technological product E-book regarding domestic property violence, informing what it is, how it occurs, the available protection network, the step-by-step guide to requiring urgent protective measures, especially the granting of food to increase the chances of postponing the protective measure. The historical-dialectic method was used to analyze the material from a bibliographical research on national legislation, an integrative review of scientific literature related to the topic and a documentary research carried out at the Police Station. Data collected from a qualitative approach in order to better understand the contextual and/or underlying aspects of the texts. The results of the documentary research in the Police Inquiries indicated in the research locus the average profile of the victim as a young woman, with a child, who does not study or work and lives in an informal relationship with the aggressor who, in turn, was found to be treating if a young man, with low education, given to drinking alcohol or drugs, in occupations without formal employment or unemployed. The analysis of the victims' narratives indicated the existence of multifaceted patrimonial violence (far beyond the average profile), materialized by actions that are sometimes subtle, sometimes hostile, which make the victim vulnerable, preventing them from qualifying, working or building a network of relationships. In response to this fact, an increase in the demand for protective measures was observed, a possible indication of a reduction in the victim's tolerance to domestic violence. Finally, the existence of a support network at the research site was verified, carrying out important prevention and rehabilitation actions for the victim, although there was no full integration between these bodies. As a result, an E-book entitled “What You Need to Know About Patrimonial Violence Against Women” was produced, containing information necessary to combat property violence, the step-by-step guide to the victim's rights in the face of a case of violence, with the aim of to improve access to knowledge of public policies, rights, resources and legal mechanisms available, whether for women victims of property crimes by their spouses or partners, or for women who have never been victims of such crimes, since knowledge is power.